2013
DOI: 10.1136/bcr-2012-007182
|View full text |Cite
|
Sign up to set email alerts
|

IgE-mediated cow milk allergy and infantile colic: diagnostic and management challenges

Abstract: SUMMARYCow milk allergy (CMA) is a common problem affecting 2-3% of children and is the most prevalent food allergy in infancy. Infantile colic is also a common problem in the first year of life. A frequent practice among physicians is to recommend a dairy-free diet to breastfeeding mothers and infants in cases of infantile colic. However, recent studies suggest that late introduction of potentially allergenic foods may increase the risk of developing a life-threatening food allergy. We describe two infants ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Studies have also found that the elimination of cow's milk for a period of time from the diet increases the risk of cow's milk allergy, suggesting that ongoing ingestion of cow's milk, once introduced, may play a role in cow's milk allergy prevention. 20,21 In a recent prospective observational study of infants with food proteineinduced allergic proctocolitis, there was a significant association between food proteineinduced allergic proctocolitis and development of IgE-mediated cow's milk allergy (OR, 5.4; 95% CI, 1.4-20.8), further supporting ongoing ingestion as a means of cow's milk allergy prevention. 22 It is important to note that several of the studies supporting a role of early cow's milk ingestion in the prevention of cow's milk allergy have also included, as part of the study design, ongoing regular cow's milk ingestion, raising the possibility that it is the consistent ingestion in these studies, instead of early exposure, that may be protective.…”
Section: The Role Of Consistent Cow's Milk Ingestion In the Prevention Of Cow's Milk Allergymentioning
confidence: 99%
“…Studies have also found that the elimination of cow's milk for a period of time from the diet increases the risk of cow's milk allergy, suggesting that ongoing ingestion of cow's milk, once introduced, may play a role in cow's milk allergy prevention. 20,21 In a recent prospective observational study of infants with food proteineinduced allergic proctocolitis, there was a significant association between food proteineinduced allergic proctocolitis and development of IgE-mediated cow's milk allergy (OR, 5.4; 95% CI, 1.4-20.8), further supporting ongoing ingestion as a means of cow's milk allergy prevention. 22 It is important to note that several of the studies supporting a role of early cow's milk ingestion in the prevention of cow's milk allergy have also included, as part of the study design, ongoing regular cow's milk ingestion, raising the possibility that it is the consistent ingestion in these studies, instead of early exposure, that may be protective.…”
Section: The Role Of Consistent Cow's Milk Ingestion In the Prevention Of Cow's Milk Allergymentioning
confidence: 99%
“…Незважаючи на велику кількість опублікованих досліджень, етіологія і патогенез дитячої кольки залишаються неясними і вважаються багатофакторними, що обумовлює складнощі вибору стратегії для розв'язання даної проблеми. Але завжди треба пам'ятати про те, що частина кольок -це імовірна гастроінтестинальна алергія до білка коров'ячого молока (АБКМ) (приблизно 25 % дітей із помірними або вираженими симптомами кольок як причину мають саме АБКМ [19]); частина як етіологічний фактор має дисахаридазну (лактазну) недостатність, характерну для дітей раннього віку; ще в багатьох немовлят кольки є про явом незрілості ентеральної нервової системи, яка обумовлює алодинію -сприйняття небольових стимулів як больових [20].…”
Section: частота функціональних гастроінтестинальних розладів є надзвunclassified
“…Food allergic reactions may trigger an eczematous rash in 30-40% of children with moderate-to-severe atopic dermatitis. [21][22][23][24][25] Pollen/Food Allergy Syndrome (also see Chapter 46) Pollen-food allergy syndrome (oral allergy syndrome) is a common disorder in which oral symptoms, itching of the throat and occasionally mild oral edema occur immediately upon the ingestion of certain foods, most commonly raw fruits and vegetables, but also certain nuts, e.g. There does not appear to be a single pattern of presentation, but careful observations by families can often make the connection, especially when parents are instructed on the typical presentation.…”
Section: Cutaneous Symptomsmentioning
confidence: 99%